2020
DOI: 10.1186/s13765-020-00547-5
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in glucose metabolism of streptozotocin-induced diabetes inbred mice (C57BL/6J)

Abstract: Considering that sex differences in glucose metabolism are observed in mice, researchers unconsciously use male mice to reduce variations by an estrogen cycle in female mice. In this study, we investigated the sex differences in glucose homeostasis in streptozotocin (STZ)-induced diabetes inbred mice (C57BL/6J). The C57BL/6J male and female mice were injected with or without STZ (40 mg/kg) for 5 consecutive days. Levels of fasting blood glucose (FBG), glycosylated hemoglobin (HbA1C), lipid profiles, oral gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Not only is vascular catheterization less technically challenging in the rat compared to the mouse, but mice require infusion of donor blood to replace erythrocytes and sustain hematocrit during clamping procedures, which results in larger colony number and more complex experimental design (137). Independently of rodent model choice, however, blood glucose assessments must take into consideration; strain (40,139), age (140,141), sex (142)(143)(144), fasting length (137,145) and husbandry (146)(147)(148) as all of these parameters differentially impact glucose homeostasis and the translatability of each model to human physiology (discussed in detail in 7,9). Nonmammalian species, while having critical distinctions in their mechanisms of glucose homeostasis, particularly with respect to the brain, offer unique opportunities afforded by their genetic tractability, lower cost, and fecundity.…”
Section: Resultsmentioning
confidence: 99%
“…Not only is vascular catheterization less technically challenging in the rat compared to the mouse, but mice require infusion of donor blood to replace erythrocytes and sustain hematocrit during clamping procedures, which results in larger colony number and more complex experimental design (137). Independently of rodent model choice, however, blood glucose assessments must take into consideration; strain (40,139), age (140,141), sex (142)(143)(144), fasting length (137,145) and husbandry (146)(147)(148) as all of these parameters differentially impact glucose homeostasis and the translatability of each model to human physiology (discussed in detail in 7,9). Nonmammalian species, while having critical distinctions in their mechanisms of glucose homeostasis, particularly with respect to the brain, offer unique opportunities afforded by their genetic tractability, lower cost, and fecundity.…”
Section: Resultsmentioning
confidence: 99%
“…Type 2 diabetes is a disorder of glucose metabolism, with a metabolic phenotype that differs according to sex [ 10 ]. Our group reported that male inbred mice (C57BL/6J) had higher hyperglycemia than female mice after STZ injection [ 9 ]. In this study, we investigated whether the genetic background of the mice was important for the development of hyperglycemia and whether female hormones such as estrogen play a role in glucose metabolism after STZ injection.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we induced diabetes with streptozotocin (STZ) in C57BL/6J mice, which are preferentially used in studies with inbred mouse strains [ 9 ]. We confirmed that there were phenotypic differences according to sex in the diabetic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, there was an approximately 4.5-fold sex difference in insulin levels with females having lower values than males. In C57BL/6J mice, a clear sex difference in streptozotocin-induced diabetes has been described with females being more resilient to the treatment [34]. In human studies, women are generally more insulin sensitive than men, a difference which seems to diminish in the development of type 2 diabetes [35].…”
Section: Effects Of Diet Sex and Tamoxifenmentioning
confidence: 99%